Produção de cerveja artesanal a partir de malte germinado pelo método convencional e tempo reduzido de germinação - Ferreira, Artur de Souza (2014)
In brewing stands out among the ingredients malt, from germinated barley. During the germination process of barley, the action of the enzyme β-glucanase promotes the reduction of β-glucans content. Incomplete germination can result in an excess of β glucans, resulting in undesirable problems in colloidal properties of beer, such as turbidity and viscosity increase. In order to optimize the production of malt beer, it is proposed in this study reducing the germination of barley time from 96 to 64 h with application of the enzyme β-glucanase at concentrations of 0, 25, 50 and 100 mg.kg-1. To compare the applicability of the produced malt, handmade beers were prepared with characteristics that differ between the time of germination and the addition or absence of β-glucanase enzyme, and evaluated their physical-chemical, microbiological and sensory characteristics. The expected turbidity for formulations with lower concentrations of enzyme was not seen in determining this physical-chemical parameter, for a probable suspension of solids in the sample by the absence of clarification processes in the development of handmade beers. From the sensory profile of the samples, performed after statistical analysis of mean variance for p ≤ 0.05, we observe similarities between beers with normal germination time (96 h) and formulation with reduced germination time (64 h) plus addition of 50 mg.kg-1 enzyme, allowing the germinated malt production with a smaller period of time, without changing the quality of the final product.